BIOSORPTION COPPER (II) BY SEAWEED PETREATED LESSONIA TRABECULADA - Rivera, Jilver (2004)
The conditions of maximum biosorption of Copper (ll) have been determined on dry algae Lessonia trabeculata. The optimal biosorption has been obtained at pH = 4,0, initial concentration = 500mg/l, size of particle of biosorbent (250 < P < 500 um). The adsorption isotherms fitted well with Langmuir and Freundlich models. The maximum adsorption was determined to be qm= 90,54 mg/g